Thyroid Ultrasound‐Guided Fine‐Needle Aspiration Cytology Results: Observed Increase in Indeterminate Rate over the Past Decade. (24th January 2017) - Manning, Amy M.; Yang, Huaitao; Falciglia, Mercedes; Mark, Jonathan R.; Steward, David L.
Abstract : Objectives: To evaluate changes in distribution of reported thyroid nodule fine‐needle aspiration (FNA) cytopathology results since implementation of the Bethesda classification and revised 2015 American Thyroid Association (ATA) guidelines for selecting nodules for biopsy. Study Design: Retrospective review. Setting: Tertiary academic medical center. Subjects and Methods: Evaluation of ultrasound (US)–guided thyroid FNA by a single surgeon using 2015 ATA nodule selection criteria and Bethesda reporting on 211 thyroid nodules in a 1‐year period (2015). Comparison is made to an earlier sample wherein any nodule >1 cm underwent US FNA with cytology reported prior to Bethesda consensus (2006). Results: The current cohort involved mostly women (79%); nodules ranged from 1 to 7 cm (mean ± SEM, 2.4 ± 0.07 cm). Mean ± SEM age was 53.5 ± 1.1 years. Bethesda reporting yielded 6% nondiagnostic, 57% benign, 3% malignant, and 34% indeterminate (27% atypia of undetermined significance [AUS]/follicular lesion of undetermined significance [FLUS], 4% follicular neoplasm [FN]/Hürthle neoplasm [HN], and 2% suspicious for malignancy [SFM]). The malignancy rate in indeterminate nodules was 26% (18% AUS/FLUS, 33% FN/HN, and 80% SFM). Age, sex, or nodule size did not correlate with indeterminate cytology. The comparator sample of 447 nodules had significantly different distribution, with 7% nondiagnostic, 80% benign, 5% malignant, and 8% indeterminate ( P <. 00001). Conclusion: We observed a significantly increased proportion of indeterminate cytology and corresponding decrease in benign nodules compared with an earlier sample, predominately from an increase in AUS/FLUS. Multiple factors are likely involved, including selection of sonographically suspicious nodules for biopsy based upon 2015 ATA guidelines coupled with cytopathological interpretation by a new generation of cytopathologists trained in the era of Bethesda reporting; further study is required to make a definitive conclusion.